МИНЕРАЛОГИЯ РОССЫПНЫХ ПРОЯВЛЕНИЙ АЛМАЗОВ АНГАРО-УДИНСКОГО МЕЖДУРЕЧЬЯ ЮГА СИБИРСКОЙ ПЛАТФОРМЫ - Егоров К.Н.; Кошкарев Д.А.; Зинчук Н.Н.; Денисенко Е.П.; Заравняев В.А. (My University, 2006)
The paper presents new data on mineralogy of diamond-bearing placers occurring in the interfluvial area between the Angara and Uda rivers. It is shown, for the first time, that minerals - indicators for diamond arc detected in all the placers known there. Diamonds of various size and morphology were identified in flood-plain deposits and channel fill of Chuksha and Talaya (right tributary of the Udinsky Tanguy river) rivers. As diamonds so the minerals-indicators have come into the placer-bearing alluvial deposits from different and separated sources. Small pyropcs, chromospinelides of the III-IV preservation classes and the mechanically eroded diamonds arc related to erosion of the Lower Carboniferous rocks of Baycronovskaya scries. Angular grains of pyropcs, pyrope-almandincs, well preserved low Fc chromites and chromodiopsides may associate with diamonds without signs of mechanical erosion from the Middle Paleozoic or Mezozoic kimberlitic (or lamproitic) source. Pyrope-grossular-almandinc scries garnets of the I"sl preservation class make paragenesis with diamond cuboids of the H"nd variety. Rare chromcvanadium minerals (goldmanites, lavrovites) from Olkhonskaya and Sly-udyanskaya series, found also in placers between the Angara and Uda rivers, may be considered as indirect indicators for cubic diamonds of mctamorphogcnic type.
Keywords: Paleozoic; Carboniferous; Paleozoic; Paleozoic::Carboniferous